Risk of venous thromboembolism in relatives of symptomatic probands with thrombophilia: a systematic review - Langlois, Nicole J.; Wells, Philip S. (Thrombosis and Haemostasis, 2003)
Clinical equipoise exists regarding whether relatives of individuals with venous thromboembolism (VTE) and thrombophilia should be screened for thrombophilia. There have been no systematic attempts to summarize studies that have assessed the incidence of VTE in relatives. The purpose of this review was to systematically identify and review observational studies with thrombophilic relatives and to summarize their findings with respect to their risk of VTE.We conducted a systematic literature review and included nine observational studies meeting a priori inclusion criteria. Potentially eligible studies evaluated VTE incidence in relatives of index patients (probands) with symptomatic thrombophilia. In the four prospective studies, the incidence of VTE for asymptomatic family members with factor V Leiden ranged from 0.58-0.67% per year, 1.0-2.5% for protein C deficiency, 0.7-2.2% for protein S deficiency, and 4% for antithrombin deficiency. About half of all VTEs occurred during well-known risk periods but incidence rates were decreased by use of prophylaxis. No deaths from pulmonary embolism or fatal hemorrhages from anticoagulants were reported. The incidence of VTE was generally lower in the retrospective studies. The pooled relative risk from four retrospective studies for factor V Leiden carriers was 3.69 (CI 2.27, 6.00) and from two studies the pooled relative risk for deficiencies of protein C, protein S, and antithrombin was 10.58 (CI 5.38, 20.81).In conclusion, the risk of VTE events in asymptomatic relatives is low, but this may be an underestimate. Anticoagulant prophylaxis during risk periods appears to be of benefit but further research in this area is required.
Keywords: Thrombophilia; risk factors; systematic review; genetics; thrombosis